Vitamin C deficiency reveals developmental differences between neonatal and adult hematopoiesis - Phadke, Ira; Pouzolles, Marie; Machado, Alice; Moraly, Josquin; Gonzalez-Menendez, Pedro; Zimmermann, Valérie S.; Kinet, Sandrina; Levine, Mark; Violet, Pierre-Christian; Taylor, Naomi (Frontiers in Immunology, 2022)
Hematopoiesis, a process that results in the differentiation of all blood lineages, is essential throughout life. The production of 1x1012 blood cells per day, including 200x109 erythrocytes, is highly dependent on nutrient consumption. Notably though, the relative requirements for micronutrients during the perinatal period, a critical developmental window for immune cell and erythrocyte differentiation, have not been extensively studied. More specifically, the impact of the vitamin C/ ascorbate micronutrient on perinatal as compared to adult hematopoiesis has been difficult to assess in animal models. Even though humans cannot synthesize ascorbate, due to a pseudogenization of the L-gulono--lactone oxidase (GULO) gene, its generation from glucose is an ancestral mammalian trait. Taking advantage of a Gulo-/- mouse model, we show that ascorbic acid deficiency profoundly impacts perinatal hematopoiesis, resulting in a hypocellular bone marrow (BM) with a significant reduction in hematopoietic stem-progenitor cell (HSPC) frequency. This feature was coupled to a decrease in peripheral lymphoid subsets and a reduced humoral immune response. Importantly, these hematopoietic parameters showed a significantly lower dependence on vitamin C in adult Gulo-/- mice––vitamin C deficiency did not alter HSPC frequency, T cell numbers, nor immunoglobulin production. However, erythropoiesis was particularly sensitive to vitamin C deprivation during both the perinatal and adult periods, with ascorbate-deficient Gulo-/- pups as well as adult mice exhibiting impaired BM and splenic differentiation. Furthermore, in the pathological context of hemolytic anemia, vitamin C-deficient adult Gulo-/- mice were not able to sufficiently increase their erythropoietic activity, resulting in a sustained anemia. Thus, vitamin C plays a pivotal role in HSPC maintenance and differentiation during the neonatal period and is required throughout life to sustain a robust erythroid differentiation.